Raman Signal Enhancement in Suspensions Containing Submicron-Sized Particles - Sokolovskaya, O. I.; Golovan, L. A.; Tkachenko, N. B.; Yakovlev, V. V. (Bulletin of the Lebedev Physics Institute, 2025)
It is shown that for an optically inhomogeneous medium, which is a suspension of submicron-sized particles in liquid, both a noticeable increase in the time of radiation interaction with the medium and growth of the Raman scattering (RS) signal are possible compared to the medium without scatterers. The optical heterodyning method was used in experiments to measure the time delay of femtosecond pulses, which reached 1 ps in suspensions of rutile microparticles in dimethyl sulfoxide (DMSO) for different scatterer volume fraction. The photon dwell time in the suspensions decreased with with scatterer volume fraction increase for scatterer volume fraction higher than 0.001. Numerical simulation results of  femtosecond laser pulse scattering by Monte Carlo method are in good agreement with experimental data. The simulation indicates that the maximum possible growth of the Raman signal registered in the diffuse reflection direction under multiple light scattering is up to 7.5-fold compared to the case of scatterer absence in the medium. The Raman signal collected with a lens increased 3.5 times in a suspension of rutile particles in DMSO compared to the Raman signal for DMSO without scatterers. The simulation results of Raman process in a scattering medium agree well with the experimental results of Raman signal efficiency measurement.